A Pilot Study Showing Fluconazole and Flucytosine Activities against Candida glabrata are Affected by Low pH: Implications for the Treatment of Recurrent Vulvovaginal Candidiasis - Ziauddin Khan; Suhail Ahmad; Mohammad Asadzadeh (IMR Press, 2024)
Background: Candida albicans (C. albicans) and Candida glabrata (C. glabrata) are mainly associated with vulvovaginal candidiasis (VVC). Management of VVC caused by C. glabrata is particularly challenging due to its inherent reduced susceptibility to fluconazole. In this prospective laboratory-based cohort study, we investigated the effect of pH on in vitro susceptibility of Candida spp. isolates to fluconazole and flucytosine. Methods: Vaginal isolates of C. glabrata, C. albicans, Candida tropicalis (C. tropicalis) and Candida parapsilosis (C. parapsilosis) were tested for susceptibility to fluconazole and flucytosine by Epsilometer test (ETEST) strips on Roswell Park Memorial Institute (RPMI) 1640 medium at pH 7.0 and pH 4.5. Minimum inhibitory concentrations (MICs) were read after 24 h at 35 °C. Results were interpreted according to the European Committee on Antimicrobial Susceptibility testing (EUCAST) guidelines. Results: Mean fluconazole MICs (µg/mL) at pH 4.5 were significantly higher than those at pH 7.0 for C. glabrata (82.55 ± 100.32 versus 14.96 ± 7.71, respectively, p = 0.001) and C. albicans (1.32 ± 7.98 versus 0.96 ± 1.35, respectively, p = 0.017) isolates. A similar effect was not observed with C. tropicalis and C. parapsilosis isolates. In contrast, mean MICs against flucytosine were reduced at pH 4.5 compared to pH 7.0 for all four Candida spp. isolates, with this reduction being statistically significant for C. glabrata and C. parapsilosis isolates. Conclusions: Our data show that the therapeutic efficacy of fluconazole against C. glabrata and C. albicans is reduced at lower (normal vaginal) pH values while the activity of flucytosine is enhanced. Therefore, flucytosine may serve as an effective alternative for the treatment of VVC and recurrent VVC caused by C. glabrata and other Candida spp.